2022
DOI: 10.7187/gjat072022-3
|View full text |Cite
|
Sign up to set email alerts
|

Examining Trends, Themes and Social Structure of Zakat Literature: A Bibliometric Analysis

Abstract: This study specifically examines the development of zakat research from the aspects of five bibliometric indicators: (1) current development of zakat research and its distribution; (2) topic areas and themes in zakat research; (3) main contributors of zakat research; (4) current collaboration pattern in zakat studies; and (5) most influential documents in zakat literature. This study conducted a bibliometric analysis of 405 scientific papers on zakat recorded in the Scopus database until 2021. Various tools ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…(2-tailed) > 0.05, then it was found that there was no significant difference between the efficiency of zakat institutions in Indonesia and Malaysia. These findings support the result [40]. Indonesia and Malaysia have become a reference for other countries in managing zakat [41].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…(2-tailed) > 0.05, then it was found that there was no significant difference between the efficiency of zakat institutions in Indonesia and Malaysia. These findings support the result [40]. Indonesia and Malaysia have become a reference for other countries in managing zakat [41].…”
Section: Resultssupporting
confidence: 87%
“…There is still very limited research that comprehensively measures the efficiency of zakat funds from various countries. Malaysia and Indonesia are countries that have a large role in collaborative zakat research [40]. Effectiveness in collecting and distributing zakat in Indonesia and Malaysia has been proven to reduce the level of poverty.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, zakat reflects a communal spirit, demonstrating a sense of collective concern for the well-being of the community (Astuti, 2018). Beyond prayers, the act of giving zakat becomes a tangible manifestation of a Muslim's piety and faith, illustrating their commitment to Islamic principles (Wahyudi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The process of examining these articles is commonly known as bibliometric analysis. In order to comprehend the evolution of zakat accounting in terms of the volume of publications, the development of the most pertinent authors, the development of the most pertinent journals, and the development of zakat accounting-related topics in the Dimensions database, this study intends to perform a bibliometric analysis (Wahyudi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Other relevant studies include Wahyudi et al (2022) examining trends, themes and the social structure of zakat literature using bibliometric analysis; Apriliyah & Arifianto (2022) evaluated zakat related literature; Ismail & Aisyah (2021) discuss Islamic social finance using bibliometric analysis; Haidar & Satifa (2022) analyze a bibliometric approach to improving Islamic microfinance as an alternative to reducing poverty; Rusydiana (2020) examines Islamic finance and SDGs; and Tok et al (2022) explain the goals of sustainable development and Islamic social finance.…”
Section: Introductionmentioning
confidence: 99%